ISLAMIC THEOLOGY IN THE SEVENTEENTH CENTURY ACEH - Fuad Mahbub Siraj (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2020)
This paper examines ‘Abd al-Ra’ūf al-Sinkili’s concept of tawhid. Using a historical approach and content analysis, this paper argues that tawhid is an important aspect in Islam and becomes an interesting discourse in the Islamic intellectual tradition, especially Sufism. ‘Abd al-Ra’ūf al-Sinkili stated that the first commitment for a human being is to accept the Oneness of Allah, and purity it from all things inappropriate to Him with the statement of lā ilaha illā Allāh. This affirms that Allah is believed to be the only Being. There is no existence without the existence of Allah (lā ilāha illā Allāh). This statement of creed implies two meanings: to negate any existence (al-nafyu), and to confirm only one existence (al-ithbāt), which is the existence of al-Haqq (the true Being). Al-Sinkili also states that Allah is One, without our attempt to make Him One. Allah is true without a need to truth legitimation from humans.